Pengaruh Pemberian Ekstrak Jahe Merah (Zingiber Officinale R.) Terhadap Susut Masak Dan Nilai pH Pada Daging Ayam Ras Petelur Afkir dengan Konsentrasi dan Lama Perendaman yang Berbeda - Rusdi, Rusdi; Munir, Munir; Nurhaeda, Nurhaeda (Fakultas MIPA UNM, 2020)
Abstract. This study aims to determine the effect of red ginger extract (Zingiber Officinale R)Â on the pH value and cooking losses. The study was conducted in January 2018 at the Laboratory of Animal Product Processing Technology, Faculty of Agriculture and Animal Husbandry using a factorial Completely Randomized Design (RAL), where factor A (level of red ginger extract and papaya fruit skin) 0%, 25%, 50%, 75% were interacted with a factor B (soaking time) of 5 minutes, 10 minutes and 15 minutes which was repeated three times. The results showed no significant effect (P> 0.05) on the value of cooking losses. The treatment of using red ginger extract (Zingiber Officinale R)Â as a natural enzyme that had no significant effect (P> 0.05) on the pH value. In factor A (extract level) to the pH value, this can be seen from the average effect of A is J0 = 6.24%, J1 = 6.28%, J2 = 6.26% and J3 = 6.40%. In factor B (duration of immersion) does not affect the pH value that can be seen from the average effect of B is W1 = 6.14, W2 = 6.41 and W3 = 6.34. The conclusion of this study was that the administration of red ginger extract in cooking losses could decrease in the treatment of P3 = 30.46% and the pH did not significantly affect the immersion long red ginger extract.Keywords:Â Red Ginger Extract, Natural Enzymes, pH Value and Shrinkage of Cook.